Ukuran Perusahaan Memoderasi Pengaruh Good Corporate Governance, Capital Intensity, Leverage, dan Profitabilitas Terhadap Agresivitas Pajak - Nuryani Madyastuti nuryani (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The purpose of this study was to determine how firm size moderating the influences of good corporate governance, capital intensity, leverage, profitability on tax aggressiveness. The population of this research are all companies in the healthcare section which are listed in Indonesian Stock Exchange (BEI). The samples are taken by using the purposive sampling method until being obtained 16 companies. The data analysis process being used for this research is panel data regression. Based on the results of the analysis, it can be seen that the capital intensity variable has a positive effect on tax aggressiveness.